Visual Commodification: Symbolic Representation Of Materiality And Aesthetics In Contemporary Coffee Culture (A Case Study Of Purwokerto, Central Java) - Ihsan, Alfian; Mutahir, Arizal; Hariyadi, Hariyadi (Department of Sociology, Faculty of Social and Political Science, Universitas Padjadjaran, 2026)
ABSTRACTThis research investigated the socio-cultural phenomenon of the cappuccino conquest in Purwokerto by exploring how specific aesthetic elements facilitate the raise of modern coffee shop. Utilizing Roland Barthes’ semiotic approach and Fredric Jameson’s concept of commodity aestheticization, the study identified serving equipment (ceramic cups) and visual appearance (latte art) as the two primary factors constructing the image of cappuccino as a luxurious, aesthetic, and modern commodity. These elements are the